The Genetic Landscape of Systemic Rheumatic Diseases: A Comprehensive Multigene-Panel Study Identifying Key Gene Polymorphisms - Elena Rita Simula; Seyedesomaye Jasemi; Davide Cossu; Pietro Carmelo Manca; Daria Sanna; Fabio Scarpa; Gianfranco Meloni; Roberto Cusano; Leonardo Antonio Sechi (MDPI AG, 2024)
Systemic rheumatic diseases, including conditions such as rheumatoid arthritis, Sjögren's syndrome, systemic sclerosis, and systemic lupus erythematosus, represent a complex array of autoimmune disorders characterized by chronic inflammation and diverse clinical manifestations. This study focuses on unraveling the genetic underpinnings of these diseases by examining polymorphisms in key genes related to their pathology. Utilizing a comprehensive genetic analysis, we have documented the involvement of these genetic variations in the pathogenesis of rheumatic diseases. Our study has identified several key polymorphisms with notable implications in rheumatic diseases. Polymorphism at chr11_112020916 within the IL-18 gene was prevalent across various conditions with a potential protective effect. Concurrently, the same IL18R1 gene polymorphism located at chr2_103010912, coding for the IL-18 receptor, was observed in most rheumatic conditions, reinforcing its potential protective role. Additionally, a further polymorphism in IL18R1 at chr2_103013408 seems to have a protective influence against the rheumatic diseases under investigation. In the context of emerging genes involved in rheumatic diseases, like PARK2, a significant polymorphism at chr6_161990516 was consistently identified across different conditions, exhibiting protective characteristics in these pathological contexts. The findings underscore the complexity of the genetic landscape in rheumatic autoimmune disorders and pave the way for a deeper understanding of their etiology and the possible development of more targeted and effective therapeutic strategies.